Efficacy of Modified Jaipur Block in Post Herpetic Neuralgia : Modified Jaipur Block in Post Herpetic Neuralgia - Akhtar, Nadia; Shahzad, Muhammad Khurram; Hassan, Tahir; Hanif, Nazia; Naz, Asma; Anwar, Sara (Pakistan Journal of Health Sciences, 2024)
Post herpetic neuralgia (PHN), a chronic neuropathic pain arising after herpes zoster (shingles) infection is notable, if discomfort persists beyond 90 days from the initial outbreak. Objective: To determine the efficacy of Modified Jaipur Block in reducing pain in patients with Post Herpetic Neuralgia. Methods: An uncontrolled clinical trial at Sheikh Zayed Hospital, Rahim Yar Khan, from January 2023 to September 2023 included 103 post herpetic neuralgia patients aged 20-80 years. Pain severity assessed using VAS score at baseline and follow-ups; efficacy defined as >75% decrease in VAS pain score at 6 months. Statistical analysis utilized SPSS 26.0, employing paired t-tests and Chi-square tests for efficacy and subgroup analyses. Results: In 103 patients predominantly aged 51-65 years and suffering mainly from thoracic pain, the Modified Jaipur block treatment yielded substantial reductions in Visual Analogue Scale (VAS) scores. From an initial mean VAS of 8.15±1.389, scores declined significantly to 2.66±2.379 at the last follow-up (p<0.001). A notable 73.8% of patients achieved remission, while relapses were observed in 7.8%. No association between remission rates and demographic or clinical variables was detected (p>0.05). At the 6-month follow-up, 61.2% of patients demonstrated efficacy (over 75% reduction in VAS pain scores), with a significantly higher efficacy noted in cases of intermittent pain (p<0.05). Conclusions: The Modified Jaipur block treatment demonstrated significant efficacy in pain reduction. The study underscores the potential of this treatment modality for targeted pain management.